An investigation into teachers' beliefs and their teaching practices in using visual aids in teaching English vocabulary at home high schools in ben tre province : - Nguyễn, Duy Trinh (Đại học Cần Thơ, 2013)
The ultimate aim of the current student is to find out whether there is a gap between teachers' beliefs and their teaching practices in using visual aids in teaching English vocabulary at some high schools in Ben Tre Province. In addition, we also aim to investigate the resons for the gap between teachers' beliefs and their teaching pratices.